Implementation of Zabbix-Based Network Monitoring with Telegram and Web Reporting - Isnandar, Ahmad Yazid; Ridwandono, Doddy; Sembilu, Nambi (STMIK Banjarbaru, 2025)
Effective network monitoring is essential in ensuring the stability and performance of campus IT infrastructure. This study aims to implement an open-source network monitoring system using Zabbix, integrated with Telegram alerts and a web-based visualization dashboard built with Laravel Filament. The development process follows the PPDIOO methodology, encompassing stages such as planning, installation, configuration, alert integration, and dashboard development. The system was implemented for the network infrastructure of two buildings at Universitas Pembangunan Nasional